Perlindungan Konsumen Terkait Harga Barang Yang Tidak Sesuai Tertera Pada Etalase Dan Struk Belanja - Masitha, Dewi; Pesulima, Theresia Louize; Balik, Agustina (TATOHI: Jurnal Ilmu Hukum, 2022)
Introduction: Consumer protection at this time cannot be separated from trading activities.Purposes of the Research: The purpose of writing this paper is. To find out the legal protection for consumers and the responsibilities of business actors regarding inappropriate prices in storefronts and shopping receipts. Methods of the Research: The research method used is normative juridical, with a statutory and conceptual approach. The sources of legal materials used are primary, secondary, and tertiary legal materials.Results of the Research: The results show that legal protection for consumers is to protect consumer rights, namely the right of consumers to obtain correct, honest and clear information regarding the state of guaranteed services and goods and rights to be served and treated honestly and correctly without discrimination. Thus, it can be seen that if there is a difference between the price of the goods listed and the price or tariff charged at the time of payment, the lowest price or tariff shall prevail.